Peran Humas Kepolisian Resor Tangerang Selatan dalam Meningkatkan Citra Kepolisian - Barikatul Hikmah; Winda Dwi Astuti Zebua; Syifa Astasia Utari (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
With the various negative issues that have approached the Indonesian police, this can have a negative impact on the image of the police. Therefore, a maximum public relations role is needed in improving the image of the police. This research aims to find out about the role of public relations of the South Tangerang Resort Police in improving the image of the police. It is also done to find out the opinions of external parties, namely the community and journalists who partner with the South Tangerang Police regarding the role that has been carried out by public relations in improving the image of the police. The theory used is the Public Relations Role theory from Ruslan (2016), namely Communicator, Relationship, Back up Management, and Good Image Maker. The approach used in conducting this research is a qualitative approach, and uses descriptive methods using data collection techniques through interviews, documentation, and literature studies. There are four sources in this study, namely the head of the public relations section of the Tangsel Police, PS PIDM Sub Section, one of the people who live in South Tangerang and journalists who partner with the Tangsel Police. The results of this study indicate that the role of public relations of South Tangerang Police in improving the image is carried out in various ways, namely as a Communicator, Relationship, Back up Management, and Good Image Maker, the role of public relations has been carried out well, so that people can continue to believe in the police institution.